A low-firing Ca5Ni4(VO4)6 ceramic with tunable microwave dielectric properties and chemical compatibility with Ag. Issue 13 (October 2016) - Wang, Dan; Xiang, Huaicheng; Tang, Ying; Fang, Liang; Khaliq, Jibran; Li, Chunchun
Abstract: A Ca5 Ni4 (VO4 )6 low loss microwave dielectric ceramic with A site deficient garnet structure was prepared via the conventional solid state reaction method. Ca5 Ni4 (VO4 )6 sintered at 980 °C for 4 h to a relative density of 96.2% exhibits favorable microwave dielectric properties such as a permittivity of 10.9, a Q×f value of 96, 500 GHz, and a τ f value of −63.6 ppm/°C. Its large negative τ f could be compensated by forming a solid solution with LiCa2 Mg2 V3 O12, that led to improved properties with a near-zero τ f =−3.7 ppm/°C, ε r =10.2, Q × f =59, 300 GHz for 0.8Ca5 Ni4 (VO4 )6 −0.2LiCa2 Mg2 V3 O12 after sintering at 955 °C for 4 h. Further on, 0.8Ca5 Ni4 (VO4 )6 −0.2LiCa2 Mg2 V3 O12 proved to be chemically compatible with Ag electrodes, so it might be a possible candidate for LTCC applications.